(3GdTLQI GdEdgjIs - (3eMeO Hf GdSjO MjOQ GdWHGWGFj, QajY GdOjf,J (B1082 (3g` s
(3ChdgG (B:s
(3bO YdeJ Cf ddCLQGe GdSeGhjI fahSkG fGWbI eLQOI Yf GdeGOI heMQcI dgG s
(3BNQgG (B:s
(3hSdWfI GdLOi KdGK CdGa SfI hSdWfI GdOdh Cda SfI hSdWfI GdMhJ Cda Sfg Je s
(3Vef eLehY , JQJjHgG (B: (3ef U (B27 - (3U(B31s
(3GfXQg eY GdeNWhW Qbe (B110 (3ef faS GdHYKIs
(3cJHJ Hbde bdjd GdfbWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B40s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeY WgQGf (B- (3cdjI GdMbhb (B(112 (3` H(B) s
Keywords: (3Gdadcs